BepiColombo Science Investigations During Cruise and Flybys at the Earth, Venus and Mercury - Mangano Valeria; Dósa Melinda; Fränz Markus; Milillo Anna; Oliveira Joana S.; Lee Yeon Joo; McKenna-Lawlor Susan; Grassi Davide; Heyner Daniel; Kozyrev Alexander S.; Peron Roberto; Helbert Jörn; et al. (SPRINGER, 2022)
The dual spacecraft mission BepiColombo is the first joint mission between the European Space Agency (ESA) and the Japanese Aerospace Exploration Agency (JAXA) to explore the planet Mercury. BepiColombo was launched from Kourou (French Guiana) on October 20th, 2018, in its packed configuration including two spacecraft, a transfer module, and a sunshield. BepiColombo cruise trajectory is a long journey into the inner heliosphere, and it includes one flyby of the Earth (in April 2020), two of Venus (in October 2020 and August 2021), and six of Mercury (starting from 2021), before orbit insertion in December 2025. A big part of the mission instruments will be fully operational during the mission cruise phase, allowing unprecedented investigation of the different environments that will encounter during the 7-years long cruise. The present paper reviews all the planetary flybys and some interesting cruise configurations. Additional scientific research that will emerge in the coming years is also discussed, including the instruments that can contribute.